What are the current barriers to effective cancer care coordination? A qualitative study - Solomon Michael J; Butow Phyllis N; Young Jane M; Harrison James D; Walsh Jennifer; Masya Lindy (BMC, 2010)
Abstract Background National cancer policies identify the improvement of care coordination as a priority to improve the delivery of health services for people with cancer. Identification of the current barriers to effective cancer care coordination is needed to drive service improvement. Methods A qualitative study was undertaken in which semi-structured individual interviews and focus groups were conducted with those best placed to identify issues; patients who had been treated for a range of cancers and their carers as well as health professionals involved in providing cancer care. Data collection continued until saturation of concepts was reached. A grounded theory influenced approach was used to explore the participants' experiences and views of cancer care coordination. Results Overall, 20 patients, four carers and 29 health professionals participated. Barriers to cancer care coordination related to six aspects of care namely, recognising health professional roles and responsibilities, implementing comprehensive multidisciplinary team meetings, transitioning of care: falling through the cracks, inadequate communication between specialist and primary care, inequitable access to health services and managing scarce resources. Conclusions This study has identified a number of barriers to coordination of cancer care. Development and evaluation of interventions based on these findings is now required.